El proceso administrativo y la atención al cliente de la cooperativa Riobamba Ltda “Agencia Guano”, 2019 - Jessica Lizbeth, Orozco Guevara (2021)
ABSTRACT In the present work of Titling the following investigation was made which allowed to determine the operation in the Administrative Process of the Cooperative Riobamba Ltda. Guano Agency that affects customer service, was verified through the study that has a administrative process defined by the matrix, but does not enforce it reporting unconformities that affect the results proposed for the fiscal period. Chapter one begins with a brief introduction detailing the importance of customer service within the context of the companies that mention the problems they are currently experiencing. The background includes detailed research carried out by various authors on the subject of study, then continues with the background and institutional generalities. Chapter two reflects the theoretical framework regarding the two variables, detailing the importance and definitions through study sources. Chapter three establishes the research methodology through the instruments and tools that allowed the data collection, interviews, survey and direct information to develop and process the information, in order to make an analysis and comparison of results. Chapter four presents the development of the proposal that seeks to provide a solution to the previously existing problems and proceeds to issue the respective conclusions and recommendations of the objectives that were proposed in the research topic. KEYWORDS: Administrative Process, Customer Service, Strategies, Management Indicators Reviewed by : Mgs. Jacqueline Guadalupe Armijos Monar ENGLISH PROFESSOR c.c 0201712858